Price perception and repurchase intention: Mediated by brand experience and brand preference - Yovan Almukarim; Yasri Yasri (Universitas Negeri Padang, 2022)
This study aims to analyze the extent of price perception on the repurchase intention of the Erigo brand in Padang City through brand experience and brand preference as mediating variables. The population in this study were all consumers of the Erigo brand and the sample in this study were users who had bought Erigo products. The number of samples in this study were 120 respondents using purposive sampling method. The analytical technique used is SEM analysis using smart PLS3. The results of this study indicate (1) Price perception has a significant influence on repurchase intention. (2) Price perception has a significant influence on brand preference. (3) Price perception has a significant influence on brand experience. (4) Brand experience has a significant influence on brand preference. (5) Brand preference has a significant effect on repurchase intention. (6) Brand experience has a significant influence on repurchase intention. (7) There is an indirect and significant and positive effect between price perception and repurchase intention through brand experience as a mediator. (8) There is an indirect and significant and positive effect between price perception and repurchase intention through brand preference as a mediator.